Pulmonary Hypertension in Parenchymal Lung Disease. (10th October 2012) - Tsangaris, Iraklis; Tsaknis, Georgios; Anthi, Anastasia; Orfanos, Stylianos E.
Abstract : Idiopathic pulmonary arterial hypertension (IPAH) has been extensively investigated, although it represents a less common form of the pulmonary hypertension (PH) family, as shown by international registries. Interestingly, in types of PH that are encountered in parenchymal lung diseases such as interstitial lung diseases (ILDs), chronic obstructive pulmonary disease (COPD), and many other diffuse parenchymal lung diseases, some of which are very common, the available data is limited. In this paper, we try to browse in the latest available data regarding the occurrence, pathogenesis, and treatment of PH in chronic parenchymal lung diseases.